A Nationwide Cohort Study on the risk of non‐gynecological cancers in women with surgically verified endometriosis. Issue 11 (26th September 2018) - Saavalainen, Liisu; Lassus, Heini; But, Anna; Tiitinen, Aila; Härkki, Päivi; Gissler, Mika; Heikinheimo, Oskari; Pukkala, Eero
Abstract : We assessed the association of surgically verified endometriosis and risk of non‐gynecological cancers according to the type of endometriosis (i.e., ovarian, peritoneal and deep infiltrating endometriosis). All diagnoses of endometriosis combined with relevant procedural codes were identified from the Finnish Hospital Discharge Register 1987–2012. Non‐gynecological cancers diagnosed after the endometriosis diagnosis were obtained from the Finnish Cancer Registry. The cohort of 49, 933 women with surgically verified endometriosis and the sub‐cohorts of ovarian ( n = 23, 210), peritoneal ( n = 20, 187), and deep infiltrating ( n = 2, 372) endometriosis were analyzed separately. The endometriosis cohort contributed 838, 685 person‐years of follow‐up and the Finnish female population served as the reference cohort. The standardized incidence ratio (SIR) and 95% confidence interval (95%CI) was calculated for each cancer separately. The follow‐up ended at emigration, death or on the 31st of December 2014. The non‐gynecological cancer risk was not increased among women with endometriosis (SIR 1.03, 95%CI 0.98–1.08). Endometriosis was associated with an increased risk of thyroid cancer in the entire cohort (SIR 1.43, 95%CI 1.23–1.64) and in the sub‐cohorts of ovarian and peritoneal endometriosis. We found a decreased risk of mouth and pharynx cancer (SIR 0.60, 95%CI 0.41–0.80), and of pancreatic cancer (SIR 0.76, 95%CI 0.58–0.96). The incidence of basal cell carcinoma was elevated in the entire cohort (SIR 1.18, 95%CI 1.10–1.25) and in the sub‐cohorts of ovarian and peritoneal endometriosis. In conclusion, women with surgically verified endometriosis have an altered risk of only few non‐gynecological cancers. Abstract : What's new? Cancer and endometriosis share certain distinguishing characteristics, prompting researchers to study the correlation between them. Here, the authors investigated the correlation between non‐gynaecological cancers and endometriosis. Working with data from nearly 50, 000 Finnish women, they calculated that a surgically verified endometriosis diagnosis increases the risk of certain non‐gynaecological cancers, while decreasing others. Thyroid cancer risk went up by 40% and basal cell carcinoma risk increased by 20%; on the other hand, risk of oropharyngeal cancer decreased by 40% and pancreatic cancer risk dropped 34%. Overall risk of non‐gynaecological cancers, they found, was not changed.